Effect of corticosteroid therapy in patients with an acute exacerbation of chronic obstructive pulmonary disease receiving ventilatory support - Hamdy Miligi Abdalah; Wageeh Hassan Sayed; Essam Abd El-Monim (Wolters Kluwer Medknow Publications, 2021)
Background Chronic obstructive pulmonary disease (COPD) is a common, preventable, and treatable disease characterized by persistent respiratory symptoms and airflow limitation that is due to airway and/or alveolar abnormalities, usually caused by significant exposure to noxious particles or gases. The chronic airflow limitation that characterizes COPD is caused by a mixture of small airway disease (e.g. obstructive bronchiolitis) and parenchymal destruction (emphysema), the relative contributions of which vary from person to person. Aim The aim of the study was to determine the effect of systemic corticosteroids in patients with severe acute exacerbations of COPD admitted to the ICU receiving ventilatory support. Patients and methods A total of 100 patients with acute exacerbations of COPD leading to hypoxemia and respiratory acidosis with pH less than 7.35 and PaCO2 more than 45 mmHg admitted to the ICU who were receiving ventilator support (invasive or noninvasive mechanical ventilation) were included. Results It was noticed that steroid group had significantly lower duration of mechanical ventilation (4.67±2.76 vs. 2.76±1.11 days; P=0.01), ICU stay (5.33±2.87 vs. 7.89±3.36 days; P=0.04), and hospital stay (11.65±3.89 vs. 16.67±4.44 days; P=0.03). Conclusion Corticosteroid therapy was associated with significantly lower duration of mechanical ventilation, ICU stay, and hospital stay.